Vertical greenery system as public art? possibilities and challenges in Malaysian urban context - Abu Bakar, Nur Izzah; Mansor, Mazlina; Harun, Nor Zalina (Elsevier, 2014)
Integrating public art with Vertical Greenery could promote sustainable principle in public spaces. Therefore, to investigate the possibilities and challenges of integrating Vertical Greenery with public art, this paper reviews nine projects in public spaces at urban places in Malaysia, as reference studies. It explores diverse dimensions of Vertical Greenery, types of public art and how they fit each other. The findings show that there are various types, systems and methods of Vertical Greenery applied in Malaysia and in coherent with the operational definition for public art used. Yet, Vertical Greenery’s promoters deal with several challenges in encouraging its vast application in urban Malaysia.